The role of fiscal decentralization in municipal budgets: Case of the Czech Republic - Břetislav Andrlík; Martina Halamová; Lucie Formanová (DANUBE: Law, Economics and Social Issues Review, 2021)
Immovable property tax is one of the key elements of fiscal decentralization in the Czech Republic. It is the only tax that is directed to municipal budgets in the full amount. It is also the only tax the total receipts of which can be influenced by municipalities by means of corrective features. Although the significance of immovable property tax in the process of fiscal decentralization is undeniable, its role in municipal budgets is much discussed. The goal of the article is to evaluate the role of immovable property tax in budgets of Czech municipalities through its impact on the resulting balance of financial management of a particular municipality. The role of immovable property tax is assessed against its importance for the municipal budget. The data concerning financial management of municipalities, the amount of receipts of immovable property tax and the possibilities of utilization of the local coefficient in the year 2019 are analyzed in detail. The results identified by the analysis are compared with the situation in 2012 and it may be stated that although the role of immovable property tax in municipal budgets has decreased if compared with the year 2012, it still represents a significant income of Czech municipalities. At the same time, the current economic situation suggests that the importance of immovable property tax will increase in the years to come.
Keywords: 330; Immovable Property Tax; Budget Balance; Municipal Budget; Fiscal Decentralization; Local Coefficient